PENGARUH FORMALIN DAN pH TERHADAP DAYA HIDUP SPERMATOZOA SAPI YANG DISIMPAN PADA SUHU RUANGAN MAUPUN 5°C - Polmer Situmorang; E Triwulanningsih; T Sugiarti; DA Kusumaningrum; RG Sianturi (Research Center for Biology-Indonesian Institute of Sciences, 2004)
The study was conducted in Research Institute for Animal Production (RIAP)-Ciawi. Semen was collected from 3 bulls twice a week by artificial vagina (AV), diluted in Tris buffer (control) and containing of 0.0625% formalin, reducing pH to 5.5 or their combination to temporally inhibit the motility of sperm.Diluted semen were store at ambient temperature for 0, 3 and 24 hours or at 5°C for 0, 3 and 7 days.Reactivation of motility was performed by dilution of formalin and bring the pH to 7.0. In ambient temperature,formalin and pH significantly (p<0.01) inhibit the motility of sperm, but these inhibition was reversible. The percentage of motility was significantly higher(p<0.01) in formalin than in pH 5.5 or control, following 24 hours of storage periode. The inhibition effect of combination between formalin and pH was non permanent. It is show that the inhibition effect of treatments was permanent for semen stored at 5°C.